Reimaging Ecclesiology from Chinese Christian Women’s Perspectives: A Case Study of Florence Li Tim Oi - LU, Yanan (Journal of Research for Christianity in China (JRCC), 2025)
In most Protestant churches in China, women constitute approximately 70% of the Christian population and have historically played a pivotal role in establishing and nurturing these communities. However, women’s experiences are frequently marginalized in ecclesiological discourse. In this paper, I bring Chinese Christian women’s experience into ecclesiological reflection. By centering Florence Li Tim-Oi (李添嫒, 1907-1992) as the focal point of the study and reading her autobiography, The Raindrops of My Life: The Memoir of Florence Tim Oi Li, as a theological source, I explore her self-identity, ordination, resignation, ministry, and experiences of suffering within her socio-political context, as well as her contributions to the church. Through this, I propose an embodied ecclesiology from Chinese Christian women’s perspectives that reimagines the church as a community, where the dignity and agency of women are recognized, and where people find a space to survive and even flourish.